Transcriptome analysis revealed differences in gene expression in sheep muscle tissue at different developmental stages - Sailuo Wan; Mengyu Lou; Sihuan Zhang; Shuang Li; Yinghui Ling (BMC Genomic Data, 2024)
Abstract Background The analysis of differentially expressed genes in muscle tissues of sheep at different ages is helpful to analyze the gene expression trends during muscle development. In this study, the longissimus dorsi muscle of pure breeding Hu sheep (H), Suffolk sheep and Hu sheep hybrid F1 generation (SH) and East Friesian and Hu sheep hybrid sheep (EHH) three strains of sheep born 2 days (B2) and 8 months (M8) was used as the research object, and transcriptome sequencing technology was used to identify the differentially expressed genes of sheep longissimus dorsi muscle in these two stages. Subsequently, GO and KEGG enrichment analysis were performed on the differential genes. Nine differentially expressed genes were randomly selected and their expression levels were verified by qRT-PCR. Results The results showed that 842, 1301 and 1137 differentially expressed genes were identified in H group, SH group and EHH group, respectively. Among them, 191 differential genes were enriched in these three strains, including pre-folding protein subunit 6 (PFDN6), DnaJ heat shock protein family member A4 (DNAJA4), myosin heavy chain 8 (MYH8) and so on. GO and KEGG enrichment analysis was performed on 191 differentially expressed genes shared by the three strains to determine common biological pathways. The results showed that the differentially expressed genes were significantly enriched in ribosomes, unfolded protein binding, FoxO signaling pathway, glycolysis / glycogen generation and glutathione signaling pathway that regulate muscle protein synthesis and energy metabolism. The results of qRT-PCR were consistent with transcriptome sequencing, which proved that the sequencing results were reliable. Conclusions Overall, this study revealed the important genes and signaling pathways related to sheep skeletal muscle development, and the result laid a foundation for further understanding the mechanism of sheep skeletal muscle development.